A new species Micrarctia kautti (Lepidoptera: Erebidae, Arctiinae) from West China - Saldaitis, Aidas; Pekarsky, Oleg (Zootaxa, 2015)
A new tiger moth, Micrarctia kautti sp. n., from southwest China, Sichuan is described. A diagnostic comparison with Micrarctia trigona (Leech, 1899) is provided. During recent years the Chinese Arctiini have been intensively collected and explored (Dubatolov, 1996a; Dubatolov, 1996b; Dubatolov, 2003; Dubatolov, Kishida & Wu, 2005; Fang & Cao, 1984; Fang, 2000 and numerous other publications) so the discovery of a striking new species by Sergey Murzin in the Dafengding Mountains, Sichuan Province, was most unexpected.        Institutional acronyms used are as follows: ASV = Aidas Saldaitis (Vilnius, Lithuania); KNE = Kari Nupponen (Espoo, Finland); PKT = Peter Kautt (Tübingen, Germany); RMB = Ramon Macià (Barselona, Spain); WIGJ = World Insect Gallery (Joniškis, Lithuania).